2015
DOI: 10.1097/dcr.0000000000000173
|View full text |Cite
|
Sign up to set email alerts
|

Does Patient Rurality Predict Quality Colon Cancer Care?

Abstract: Background Over fifty million people reside in rural America. However, the impact of patient rurality on colon cancer care has been incompletely characterized, despite its known impact on screening. Objective Our study sought to examine the impact of patient rurality on quality and comprehensive colon cancer care. Design Using the 1996–2008 California Cancer Registry, we constructed a retrospective cohort of 123,129 patients with stage 0–IV colon cancer. Rural residence was established based on the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 24 publications
4
71
5
2
Order By: Relevance
“…Seventeen studies were conducted in Australia, 16 in the United States, 6 in Europe, 4 in Canada, and 2 in New Zealand . These studies investigated several neoplasms including female breast, male breast, cervix, colorectum, endometrium, esophagus and stomach, liver (intrahepatic cholangiocarcinoma), lung, melanoma, neuroendocrine tumours, non‐Hodgkin lymphoma, ovary, pancreas, prostate, and selected groups of cancers . Most studies used only population‐based cancer registry data, while others used data from a range of sources including hospitals, academic medical centers, or treatment services or registries; others used population‐based cancer registries linked with public and private hospitals and treatment datasets .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies were conducted in Australia, 16 in the United States, 6 in Europe, 4 in Canada, and 2 in New Zealand . These studies investigated several neoplasms including female breast, male breast, cervix, colorectum, endometrium, esophagus and stomach, liver (intrahepatic cholangiocarcinoma), lung, melanoma, neuroendocrine tumours, non‐Hodgkin lymphoma, ovary, pancreas, prostate, and selected groups of cancers . Most studies used only population‐based cancer registry data, while others used data from a range of sources including hospitals, academic medical centers, or treatment services or registries; others used population‐based cancer registries linked with public and private hospitals and treatment datasets .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one studies reported overall survival (ie, death from any cause) . The remaining studies presented cancer‐specific or relative survival, which estimate effects on death due to the cancer under study only …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite improvements in preventive and treatment opportunities for patients with colorectal and cervical cancers, rural patients are less likely to receive state‐of‐the‐art treatment. In fact, previous studies have associated residential rurality with cancer diagnosis at a later stage, inappropriate and/or underuse of treatment, and poorer survival . Across all tumor sites, high disparate mortality rates from colorectal and cervical cancers have raised concerns regarding access to cancer care …”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand rural–urban differences in the receipt of surgical care for endometrial cancer, especially as rural counties lack spatial access to gynecologic oncologist services, which may put them at greater risk of endometrial cancer mortality [25, 26]. Furthermore, multiple studies have shown that rural patients with other cancer types are less likely to have lymph nodes examined and/or to have adequate lymphadenectomy during their surgical treatment [2729]. This has not been explored for endometrial cancer patients.…”
Section: Introductionmentioning
confidence: 99%